2015
DOI: 10.1097/dss.0000000000000510
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on the Treatment of Posterior Cheek Enlargement in HIV+ Patients With Botulinum Toxin A

Abstract: Botulinum toxin A may be a less invasive treatment of posterior cheek enlargement in HIV+ patients, with advantages of a good result that is long lasting with good tolerability and minimal risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Without treatment, hypertrophic parotid glands can affect the contour and appearance of the face, which can lead to psychological issues. 11 Our prospective single-arm trial demonstrated that botulinum toxin type A injection was efficacious in improving parotid gland hypertrophy and the lateral contours of the face.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Without treatment, hypertrophic parotid glands can affect the contour and appearance of the face, which can lead to psychological issues. 11 Our prospective single-arm trial demonstrated that botulinum toxin type A injection was efficacious in improving parotid gland hypertrophy and the lateral contours of the face.…”
Section: Discussionmentioning
confidence: 83%
“…Without treatment, hypertrophic parotid glands can affect the contour and appearance of the face, which can lead to psychological issues. 11 Our prospective We selected change in size of the superficial lobe of the parotid gland (rather than the total thickness) as the primary outcome because of differences in parotid gland morphology between individual patients, because measurement of the deep boundary is not straightforward, and because deep-echo attenuation will lead to greater measuring error. 17 Ultrasound was used to measure the distance from the superficial lateral wall of the retromandibular vein to the superficial lobe of the parotid gland capsule.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human immunodeficiency virus could also cause unilateral or bilateral posterior cheek enlargement with lymphatic infiltrates or hyperplastic intraparotid lymph nodes in gland tissue. 18 These findings can be treated with intraglandular BTX-A injection. Inflammatory diseases such as Sjögren syndrome and sarcoidosis and neoplastic disease also affect the parotid gland.…”
Section: Discussionmentioning
confidence: 99%
“…This effect could be beneficial in reducing parotid gland size for patients with parotid gland hypertrophy. 21,22 However, in rare cases, this could also cause xerostomia. 18 The average width of the masseter muscle was 33.62 mm; however, the average primary horizontal spreading was 15.60 mm.…”
Section: Discussionmentioning
confidence: 99%